Transformation of Asset Management System: A Phenomenologi Cal Study of Siman Version 2 at Surabaya Sailing Polytechnic - Muhammad Ayub Qonaa Mukti; Indrawati Yuhertiana; Rida Perwita Sari (Green Publisher Indonesia, 2025)
Digital transformation in the management of State Property (BMN) requires organizational adaptation in technology, work culture, and governance. This study analyzes the transformation of the state asset management system through SIMAN Version 2 implementation at Surabaya Sailing Polytechnic using a phenomenological qualitative approach. It draws on the Theory of Organizational Change and Good Governance principles. Data came from in-depth interviews with eight system users across organizational levels, analyzed via the Stevick-Colaizzi-Keen model to identify stakeholder experience themes. Findings reveal SIMAN Version 2 improves efficiency via system integration, verification automation, and a three-tier authorization structure—yielding an 85.7% reduction in processing time, elimination of data duplication through SAKTI integration, real-time transparency, and comprehensive activity logs. Initial challenges included user resistance, slow response times with large datasets, and cultural shifts from manual to digital processes. These were overcome with over 10 training sessions, peer mentoring, and ongoing technical support. The study concludes that SIMAN Version 2 successfully drives organizational change, enhancing BMN management transparency, efficiency, and accountability in line with good governance.